PERBANDINGAN METODE ORDINARY LEAST SQUARE (OLS) DAN REGRESI ROBUST PADA PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DI JAWA TENGAH TAHUN 2013 - Muhammad Nasihin; Abdul Karim (Universitas Muhammadiyah Semarang, 2017)
High economic growth is a key condition for the sustainability of regional economic development. To measure the local economy by observing how much economic growth rate the region achieved as reflected by the increase of Gross Regional Domestic Product (GRDP). PDRB is one of the common indicators used to measure the success rate of economic development in a region / region, because thesuccess of a development depends on the ability of the region to mobilize limited resources so as to make changes in a skruktural that can encourage the overall economic growth and balanced. This study aims to analyze how big these factors affect the level of GDP of regencies / cities in Java Tengan in the period2013. Sources of data used in this study are secondary data in Central Java Central obtained from the Central Bureau of Statistics of Central Java Province in 2013. The variables used in this research are endogenous (Y) and exogenous (X) variables. Endogenous variables (Y) in the research is PDRB Agriculture while the variable (X) in the study there are 2 namely AngkaTPAK, and Wages. Using OLSmethod and ROBUST method of both methods is the best model that is on robus method. Keywords: OLS, Robust Regression,Gross Regional Domestic Product